2008
DOI: 10.1002/ijc.23612
|View full text |Cite
|
Sign up to set email alerts
|

Prospective weight change and colon cancer risk in male US health professionals

Abstract: Epidemiological studies are remarkably consistent, especially among men, in showing that overweight and obesity [body mass index (BMI) >25] are associated with increased risk of colon cancer. However, no prospective studies address the influence of weight change in adulthood on subsequent colon cancer risk. In this study, we investigated whether weight change influences colon cancer risk utilizing prospectively collected weight data. We included 46,349 men aged 40–75 participating in the Health Professionals F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 43 publications
6
53
3
1
Order By: Relevance
“…Our findings for men are comparable with those from other prospective cohort (6,18) and case-control studies (13,19,20,25) that examined weight gain since early adulthood. The Health Professionals Study reported weight gain to be positively associated with colon cancer risk; men gaining >7.5 kg per 10 years have a HR of 1.41 (18).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings for men are comparable with those from other prospective cohort (6,18) and case-control studies (13,19,20,25) that examined weight gain since early adulthood. The Health Professionals Study reported weight gain to be positively associated with colon cancer risk; men gaining >7.5 kg per 10 years have a HR of 1.41 (18).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings for men are comparable with those from other prospective cohort (6,18) and case-control studies (13,19,20,25) that examined weight gain since early adulthood. The Health Professionals Study reported weight gain to be positively associated with colon cancer risk; men gaining >7.5 kg per 10 years have a HR of 1.41 (18). One case-control study (13) reported a relative risk of 1.77 for men who gained >20 kg since age 20 years, whereas a pooled analysis of several case-control studies (including the aforementioned study) gave a relative risk of 1.5 for weight gain of >20 kg since age 20 (20).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…3 Many studies have shown that general obesity as measured by BMI is positively associated with colon or colorectal cancer in men, [4][5][6][7][8][9][10][11] whereas weaker or no associations have been found in women. 4,6,8,[12][13][14] Findings for rectal cancer risk in association with height, weight or BMI have been inconsistent and nonsignificant.…”
Section: )mentioning
confidence: 99%
“…These associations seem to be stronger for men [1][2][3]. The 'Health Professionals Follow-Up Study' that included 46,349 men over a prospective 28-year period, the 'Melbourne Collaborative Cohort Study' with 16,188 men and 23,438 women with almost a 14-year follow-up, and the 'Norwegian population-based Study' of 8,822 men and 37,357 women corroborated these findings [4][5][6].…”
mentioning
confidence: 73%